German unification and the union of Europe : the domestic politics of integration policy - Anderson, Jeffrey J. (Cambridge ; New York : Cambridge University Press, 1999)
German Unification and the Union of Europe discusses some of the most interesting questions in the study of comparative politics and international relations. The book studies the sources of continuity and change in German policy toward the European Union, set in the context of the competing pulls of integration into the EU, and unification of East and West Germany. Employing a framework of analysis premised on the interaction of interests, institutions, and ideas, the book asks: how has the domestic politics of unification influenced German policy toward Europe? Why has continuity reigned in some areas, whereas in others significant changes, sometimes reversals, have been registered?
What are the implications of this checkered pattern of outcomes for Germany and for Europe?
A new Germany in Europe? -- Unification and "Germany in Europe" -- Continuity in trade and internal market -- Mixed outcomes in energy and environment -- Change in competition policy -- Change in structural funds and the CAP -- A new Germany in Europe.
Includes bibliographical references (pages 212-224) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Union Européenne -- Allemagne; Germany -- History -- Unification, 1990.; Germany -- Relations -- Europe; Europe -- Relations -- Germany; European Union -- Germany; Germany -- Commercial policy; Germany -- Foreign relations -- Europe; Europe -- Foreign relations -- Germany; Union européenne -- Allemagne; Allemagne -- Histoire -- 1990 (Réunification); Allemagne -- Relations extérieures -- Europe; Europe -- Relations extérieures -- Allemagne; Allemagne -- Politique commerciale; Europe -- Relations -- Allemagne; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Diplomatic relations; Commercial policy; International relations; Europe; Germany; Wirtschaftsentwicklung; Wirtschaftspolitik; Duitse hereniging; Europese integratie; Allemagne -- Conditions économiques -- 1990- ...; Allemagne -- Politique et gouvernement -- 1990- ...; Allemagne -- Relations extérieures -- 1990- ...; Deutschland -- Vereinigung; Europäische Union; 1990; Electronic books; History